Hypoxia promotes osteogenesis by facilitating acetyl‐CoA‐mediated mitochondrial–nuclear communication. (24th October 2022) - Pouikli, Andromachi; Maleszewska, Monika; Parekh, Swati; Yang, Ming; Nikopoulou, Chrysa; Bonfiglio, Juan Jose; Mylonas, Constantine; Sandoval, Tonantzi; Schumacher, Anna‐Lena; Hinze, Yvonne; Matic, Ivan; Frezza, Christian; et al.
Abstract: Bone‐derived mesenchymal stem cells (MSCs) reside in a hypoxic niche that maintains their differentiation potential. While hypoxia (low oxygen concentration) was reported to critically support stem cell function and osteogenesis, the molecular events triggering changes in stem cell fate decisions in response to normoxia (high oxygen concentration) remain elusive. Here, we study the impact of normoxia on mitochondrial–nuclear communication during stem cell differentiation. We show that normoxia‐cultured murine MSCs undergo profound transcriptional alterations which cause irreversible osteogenesis defects. Mechanistically, high oxygen promotes chromatin compaction and histone hypo‐acetylation, particularly on promoters and enhancers of osteogenic genes. Although normoxia induces metabolic rewiring resulting in elevated acetyl‐CoA levels, histone hypo‐acetylation occurs due to the trapping of acetyl‐CoA inside mitochondria owing to decreased citrate carrier (CiC) activity. Restoring the cytosolic acetyl‐CoA pool remodels the chromatin landscape and rescues the osteogenic defects. Collectively, our results demonstrate that the metabolism–chromatin–osteogenesis axis is perturbed upon exposure to high oxygen levels and identifies CiC as a novel, oxygen‐sensitive regulator of the MSC function. Synopsis: While low oxygen conditions are established to support mesenchymal stem cell (MSC) differentiation, the impact of normoxia on MSCs remains unclear. This work uncovers increased oxygen levels as a regulator of acetyl‐CoA subcellular localization, impairing histone acetylation and osteogenic differentiation. A shift from 2 to 21% O2 results in irreversible loss of osteogenic differentiation capacity in murine MSCs. Normoxia is accompanied by histone hypo‐acetylation and global chromatin compaction, particularly on promoters and enhancers of osteogenic genes. Histone hypo‐acetylation is caused by reduced activity of mitochondrial citrate transporter (CiC) and impaired export of acetyl‐CoA to the cytosol. Abstract : Exposure of mesenchymal stem cells to normoxia impairs osteogenic differentiation due to altered acetyl‐CoA localization within the cell.